HPMA copolymers containing doxorubicin bound by a proteolytically or hydrolytically cleavable bond: comparison of biological properties in vitro - Kovár, M; Kovár, L; Subr, V; Etrych, T; Ulbrich, K; Mrkvan, T; Loucká, J; Ríhová, B (Journal of controlled release, 2004)
N-(2-Hydroxypropyl)methacrylamide (HPMA) copolymer carrier containing the anticancer drug doxorubicin bound either by a proteolytically degradable bond (non-targeted PK1 or targeted with alpha-CD71 mAb) or by a hydrolytically degradable bond were synthesised and tested in vivo for various biological properties. Mouse 38C13 B-cell lympoma was used as a well established and defined cell line for this study. 38C13 cells are sensitive to free doxorubicin and IC50 was very low, about 0.014 microM. PK1 showed a strongly decreased cytostatic effect, IC50 being 12.6 microM. alpha-CD71 targeted conjugate, which can be considered as an antibody-targeted form of PK1, had IC50 0.358 microM. HPMA copolymer with doxorubicin bound via a hydrolytically sensitive bond (HYD conjugate) showed a high cytostatic effect with IC50 about 0.052 microM. We demonstrated that HYD conjugate inhibited DNA synthesis and induced p21(Waf1/Cip1) protein expression (p21(Waf1/Cip1) is cyclin-dependent kinase inhibitor which blocks cell cycle progression) as quickly as free doxorubicin, whereas PK1 acted much more slowly. Similarly, apoptosis induction measured by Annexin V binding and Caspase 3 activity was detected later after incubation of cells with PK1 or alpha-CD71 targeted conjugate. Apoptosis was manifested by elevation of bax and bad mRNA levels, which was much more rapid and intense in the case of free doxorubicin and HYD conjugate. Expression of antiapoptotic genes as well as cyclin-dependent kinases was surprisingly not affected.
Keywords: receptory transferinu; Genes, myc; Caspase 3; Thymidine; kaspasa 3; tritium; doxorubicin; myši; Ligands; Cell Proliferation; proteiny buněčného cyklu; nádorové buněčné linie; Caspases; Cell Line, Tumor; apoptóza; Cell Cycle Proteins; Cell Membrane; Gene Expression; Hydrolysis; protein Bad; hydrolýza; Tritium; Inhibitory Concentration 50; protein X asociovaný s bcl-2; Mice; Animals; Cell Cycle; proliferace buněk; exprese genu; Receptors, Transferrin; buněčný cyklus; Acrylamides; Doxorubicin; inhibiční koncentrace 50; preklinické hodnocení léčiv; Cyclin-Dependent Kinase Inhibitor p21; Apoptosis; bcl-Associated Death Protein; zvířata; DNA; protoonkogenní proteiny c-bcl-2; ligandy; Carrier Proteins; Drug Evaluation, Preclinical; Hydrazones; bcl-2-Associated X Protein; inhibitor p21 cyklin-dependentní kinasy; thymidin; messenger RNA; Proto-Oncogene Proteins c-bcl-2; geny myc; buněčná membrána; transportní proteiny; kaspasy; akrylamidy; hydrazony; RNA, Messenger